Status signals : a sociological study of market competition - Podolny, Joel M. (Joel Marc) (Princeton University Press e-book., 2008)
Why are elite jewelers reluctant to sell turquoise, despite strong demand? Why did leading investment bankers shun junk bonds for years, despite potential profits? Status Signals is the first major sociological examination of how concerns about status affect market competition. Starting from the basic premise that status pervades the ties producers form in the marketplace, Joel Podolny shows how anxieties about status influence whom a producer does (or does not) accept as a partner, the price a producer can charge, the ease with which a producer enters a market, how the producer's inventions.